Perceptual Balance, Stability, and Aesthetic Appreciation: Their Relations Depend on the Picture Type. (June 2019) - Hübner, Ronald; Fillinger, Martin G.
It is widely assumed that the aesthetic appreciation of a picture depends, among others, on how well the picture's composition is perceptually balanced, where "perceptual balance" is often defined analogous to mechanics. To what extent this metaphor holds for different picture types, however, is still open. Therefore, in this study, we examined the relationship between balance, liking, and some objective measures with pictures from an aesthetic sensitivity test. These stimuli could be divided into single-element, multiple-element, and dynamic-pattern pictures. The results show that "balance" is interpreted differently, depending on the stimulus type. Whereas "mechanical" balance was applied to assess single-element pictures, the balance of multiple-element and dynamic-pattern pictures was rated more in the sense of gravitational stability. Only for the multiple-element stimuli, there was a positive relation between balance/stability and liking. Together, our findings show that there are different types of balance, and that their relation with liking depends on the picture type.